PERAN STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN DI ERA KOMPETISI GLOBAL - Hanif Yusuf; Dimas Srilaksono; Andri Adinda Budiarto (Jurnal Riset Multidisiplin Edukasi, 2026)
Employee productivity is a crucial indicator in assessing the extent to which an organization is able to utilize its potential. High productivity reflects the effectiveness of work processes, time utilization, and the quality of results achieved. Conversely, low productivity can impact an organization's competitiveness amidst the pressures of global competition. Therefore, increasing employee productivity is inextricably linked to the role of management in designing appropriate HR policies and strategies. This study aims to determine the role of human resource management strategies in increasing employee productivity in the era of global competition. This study used a systematic literature review (SLR) method. The results indicate that human resource management strategies play a crucial role in increasing employee productivity in the era of global competition. Human resource management is a key factor capable of creating competitive advantage through competency development, the establishment of a positive work culture, and the implementation of a targeted performance system. Strategies implemented in a planned and integrated manner have been proven to have a significant impact on increasing individual and organizational work effectiveness.